Novel ionic liquid-infused PVA-based anion exchange membranes boosting bioelectricity yield from microbial fuel cells - Richa Tomar; Soumyajit Chandra; Soumya Pandit; Mudassar Shahid; Kuldeep Sharma; Swetha Raj; Geetha S.J; Sanket J. Joshi (Heliyon)
The goal of this research is to develop and characterize low-cost NH4I doped polyvinyl alcohol (PVA)–4-ethyl-4-methylmorpholiniumbromide (ionic liquid) anion exchange membranes (AEM) and its application for membrane cathode assembly. Physical characterization like FTIR, POM, and XRD notified the functional groups, basic structure, and amorphosity of the produced membrane, and it was employed in single-chambered microbial fuel cells (sMFCs) as a separator. The membranes in terms of oxygen diffusion, proton conductivity, and ion exchange capabilities were evaluated. PVA–ionic liquid composite membrane had a greater volumetric power density (PD) with a rise in the ionic liquid concentration, owing to lower internal resistance and reduced biofouling. Ionic conductivity also reduces as loading increases over a certain level of concentration. The incorporation of ionic liquid into the membrane had a considerable impact on impedance minimization (an enhancement in anionic conductivity) and biofouling. When MFC was used with a PVA–ionic liquid-based membrane cathode assembly (MCA), the highest PD of 7.98 W/m3 was attained which is better than other composite membranes. The MCA surface area boosted the power output. The PVA–ionic liquid composite membrane proved to be a viable alternative to the more costly commercially available MFC membrane. This paper's novelty lies in synthesizing ammonium iodide (NH4I) doped PVA-ionic liquid membrane and further utilizing it as a separator in MFC. Also, this study demonstrates the membrane's potential for enhancing MFC performance, establishing it as a viable alternative to expensive commercial membranes.